2020
DOI: 10.1111/meca.12300
|View full text |Cite
|
Sign up to set email alerts
|

Functional income distribution, capacity utilization, capital accumulation and productivity growth in Turkey: A post‐Kaleckian analysis

Abstract: The role and function of income distribution in economic growth has been discussed more intensively since the financial and economic crisis that burst out more than a decade ago. The neoclassical economic analysis took invariability of the relative shares of labor and capital in national income for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Our findings are in line with those of Yılmaz (2015), however, Onaran and Galanis (2014) had found the Turkish economy to be wage-led both domestically and overall. Domestic vs. overall economy distinction is not pertinent in other studies on Turkiye (Onaran and Stockhammer, 2005;Bölükoğlu, 2019;Kurt, 2020) and the overall demand regime is found to be wage-led in those.…”
Section: Demand Regimementioning
confidence: 89%
See 1 more Smart Citation
“…Our findings are in line with those of Yılmaz (2015), however, Onaran and Galanis (2014) had found the Turkish economy to be wage-led both domestically and overall. Domestic vs. overall economy distinction is not pertinent in other studies on Turkiye (Onaran and Stockhammer, 2005;Bölükoğlu, 2019;Kurt, 2020) and the overall demand regime is found to be wage-led in those.…”
Section: Demand Regimementioning
confidence: 89%
“…While Bölükoğlu (2019) confirmed the prevalence of a wage-led demand regime in Turkiye, Yılmaz's (2015) findings pointed out a profit-led economy. In the literature, the majority of the post-Keynesian empirical studies examined demand regimes, however, Kurt (2020Kurt ( , 2021, based on the theoretical model of Hein and Tarassow (2010) demand and productivity regimes together in Turkiye and the US, respectively. The author found that the demand regime in the former is wage-led, nevertheless taking into account that the productivity regime renders the economy unstable.…”
Section: Review Of Empirical Researchmentioning
confidence: 99%
“…Çalışmanın Türkiye için bulgusu, Kurt (2020)'un Türkiye için yaptığı çalışmanın sonuçlarıyla uyumludur. Kurt (2020) çalışmasında reel döviz kurunun net ihracata etkisinin negatif olduğu ileri sürülmektedir. Kapasite kullanım oranı ile net ihracat arasında Türkiye için uzun dönemde istatistiksel olarak anlamlı bir ilişki elde edilirken, Brezilya için anlamsız bir ilişki elde edilmiştir.…”
Section: Net İhracat Denklemiunclassified